2007
DOI: 10.1111/j.1360-0443.2007.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharmaceutical company funding on results of randomized trials of nicotine replacement therapy for smoking cessation: a meta‐analysis*

Abstract: Compared with independent trials, industry-supported trials were more likely to produce statistically significant results and larger odds ratios. These differences persisted after adjustment for basic trial characteristics. Although we had no data on the amount of funding for each trial, it is possible that more resources led to higher treatment compliance and therefore greater efficacy in industry-supported trials. Differences can also possibly be explained by publication bias with several small, null-effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 21 publications
1
48
1
Order By: Relevance
“…The need for these committees grew out of the well-understood financial conflicts of interest that exist in many clinical trials. The sponsor of a trial may be the company manufacturing the product, and any intentional or unintentional influence can distort the study design, analysis and interpretation of results for the ultimate financial benefit of the manufacturer at the cost of the accuracy of the science and the health benefit to the consumers 37,38 . Non-financial conflicts of interest also exist, such as the beliefs and preconceptions of individual scientists and the stakes that researchers have in obtaining publishable results in order to progress their career 39,40 .…”
Section: Improving Methodological Trainingmentioning
confidence: 99%
“…The need for these committees grew out of the well-understood financial conflicts of interest that exist in many clinical trials. The sponsor of a trial may be the company manufacturing the product, and any intentional or unintentional influence can distort the study design, analysis and interpretation of results for the ultimate financial benefit of the manufacturer at the cost of the accuracy of the science and the health benefit to the consumers 37,38 . Non-financial conflicts of interest also exist, such as the beliefs and preconceptions of individual scientists and the stakes that researchers have in obtaining publishable results in order to progress their career 39,40 .…”
Section: Improving Methodological Trainingmentioning
confidence: 99%
“…[288][289][290][291][292][293][294][295][296][297][298] Jorgensen et al compared Cochrane reviews with industry-supported meta-analyses of the same drugs. They found that industry-supported metaanalyses of drugs 'were less transparent, had few reservations about methodological limitations of the included trials, and had more favourable conclusions than the corresponding Cochrane reviews'.…”
Section: -284mentioning
confidence: 99%
“…The study by Greene et al [1] is a useful complement to our 2007 study, in which we observed a larger effect for NRT in industry-sponsored trials than in independent trials [2]. We offered two explanations for this result.…”
mentioning
confidence: 63%